EFFICIENCY OF MODERN AGROTECHNOLOGICAL METHODS OF HARICOT (COMMON BEAN) CULTIVATION UNDER IRRIGATION IN ASTRAKHAN REGION - Tyutyuma Natalia V.; Bondarenko Anastasia N.; Egorova Galina S.; Kuznetsova Nadezhda V. (Мелиорация и гидротехника, 2023)
Purpose: to determine the most effective options for irrigation regimes, growth stimulation that meet the requirements of resource-saving technology for common beans cultivation under the conditions of Astrakhan region. Materials and methods. To study the effect of pre-sowing inoculation of planting material (seeds) of beans, as well as irrigation regimes, a field experiment was set up. The object of the study was the common bean variety Rubin, admitted to Nizhnevolzhsky region. Field studies and observations were carried out according to generally accepted methods. The statistical analysis of the obtained results was carried out according to the B. A. Dospekhov method. Results. In the course of the study, it was found that the primary criteria in the formation of common bean variety Rubin high yields are the water regime, mineral nutrition and the biological potential of leguminous plants. Pre-sowing inoculation with various biofertilizers had a positive effect on the formation of the yield of the studied crop and, accordingly, on the crop structure elements. This was especially evident in the variants with the application of Azotovit with irrigation regimes of 65-70-65 and 70-75-70 % of the minimum moisture capacity (MC). The crop yield was 4.2–5.4 t/ha, which differed significantly from the control variant. Conclusions. Based on the results of the study, it should be noted that the maximum yield options differed by the maximum number of beans per plant (from 19.0 to 25.6 pcs.), the number of seeds 45.2–63.0 pcs., and also the weight 1000 grains from 352.0 to 364.0 g. The increase relative to the control without treatments was from +2.2 to +3.1 t/ha, depending on the irrigation regime of the studied crop. The most significant profit, as well as the level of profitability, was obtained in two options with irrigation regimes of 65-70-65 and 70-75-70 % MC when inoculating bean seeds with Azotovit.